Genetic, cellular and immune approaches to disease therapy: past and future - Nabel, Gary J (Nat Med, 2004)
Advances in immunology and molecular genetics have accelerated our understanding of the genetic and cellular basis of many diseases. At the same time, remarkable progress in recombinant DNA technology has enabled the development of molecular and cellular treatments for infectious diseases, inherited disorders and cancer. This Perspective is intended to give a sample of the progress over the past ten years in cellular, genetic and immune therapy of disease. During this time, monoclonal antibody technology and cellular transplantation have begun to come of age in biomedicine. Innovations in gene delivery have not only catalyzed the nascent field of human gene therapy, but may also ultimately impact human health by advancing recombinant vaccine technology.